O IMPACTO DA APOSENTADORIA NO PROCESSO DE TRANSFERÊNCIA DO CONHECIMENTO SOB A ÓTICA DA ARSO (ANÁLISE DE REDES SOCIAIS E ORGANIZACIONAIS) - Menezes, Eduardo Heitor Alves de (2013)
The organizational environment has been learning continuously generate knowledge and its main form of transfer is through contact between people, so understanding how is this interaction is essential. One way to get this understanding is with the help of the technique of social network analysis. This paper presents the applicability of the technique within the context of Knowledge Management, showing its value for understanding the flow of tacit knowledge within an organization, pointing out the critical actors and demonstrating the impact caused by the exit of the servers by granting retirement. Therefore, we carried out an exploratory, descriptive literature and case study conducted through a questionnaire that was designed to obtain data on social networks organizational information, trust and friendship between the servers CNEN, headquartered in the city of Rio de Janeiro, with activities related to Human Resources, selected through non-probabilistic method due to its accessibility. The data were processed in software Ucinet for Windows 6 for Windows - version 6.483 in parallel to the program Netdraw 2134, which allowed the mapping and analysis of informal social networks showing the location and view more clearly who are actors and critical paths driven by organizational knowledge, facilitating the sharing of knowledge. The main findings expose the analyzed networks suffer significant declines, jeopardizing the flow of knowledge.